2021
DOI: 10.21926/rpm.2104047
|View full text |Cite
|
Sign up to set email alerts
|

Pozzolanic and Cementing Activity of Raw and Pyro-Processed Saudi Arabian Red Mud (RM) Waste

Abstract: This paper investigates the composition, properties and reactivity of a red mud waste generated in Saudi Arabia with a view to find alternative materials to replace construction binders of high environmental impact. The phase transformation triggered by the sintering of the RM up to 1000°C is determined with thermal and X-Ray Diffraction analyses. Reactivity is investigated with chemical and physical methods including the Chapelle test, setting times, mechanical index and microscopy. The RM is clearly pozzolan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…In this study, a uniform contact time is considered in all the samples with each heavy metal ion. alumina compounds (Table 1), which is in agreement with the previous studies [24][25][26]. However, calcination beyond 700ºC causes decarbonation of calcite (calcium carbonate), and quick lime formation happens, adversely affecting the reactivity.…”
Section: Atomic Absorption Spectroscopy (Aas)supporting
confidence: 91%
“…In this study, a uniform contact time is considered in all the samples with each heavy metal ion. alumina compounds (Table 1), which is in agreement with the previous studies [24][25][26]. However, calcination beyond 700ºC causes decarbonation of calcite (calcium carbonate), and quick lime formation happens, adversely affecting the reactivity.…”
Section: Atomic Absorption Spectroscopy (Aas)supporting
confidence: 91%
“…Therefore, the thermal treatment of the bauxite increases the surface available for reaction at least up to 700 • C. The results indicate that, at a certain point after reaching 700 • C, the bauxite particles begin to agglomerate. A similar trend was obtained when sintering the red mud residue of this bauxite [25]. Other authors have also found similar trends in other bauxites.…”
Section: Physical Properties Of the Bauxitesupporting
confidence: 87%
“…The high pozzolanic index for bauxite when compared with RM and FA is largely due to the mineralogy of the bauxite including major kaolinite, gibbsite and boehmite. The major components of the bauxite's red mud are hematite, cancrinite -Na₆ Ca₂[(CO₃)₂| Al₆Si₆O₂₄]⋅2H₂O, gibbsite -Al (OH) 3 and sodalite Na 4 Si 3 Al 3 O 12 Cl [25] which, although reactive, combine less lime that the bauxite's aluminium phases in the short term.…”
Section: Reactivity By the Chapelle Testmentioning
confidence: 99%
See 2 more Smart Citations